Ida Halpern: A Post-Colonial Portrait of a Canadian Pioneer Ethnomusicologist - Chen, Kenneth (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
The work of Ida Halpern (1910–87), one of Canada's first musicologists and a pioneer ethnomusicologist, has been largely ignored. This essay illuminates her most important contribution to the musical development of this country: the documentation of Native musics. Halpern devoted some four decades to recording and analyzing over five hundred songs of the Kwakwaka'wakw, the Nuuchahnulth, the Haida, the Nuxalk, and the Coast Salish First Nations of British Columbia—a truly remarkable achievement considering that a large part of her fieldwork was conducted during a period when it was illegal for Native cultures to be celebrated, much less preserved. The author discusses the strengths and weaknesses of her methodology as well as some factors affecting the reception of her work by academic peers and by the communities she worked with. While Halpern did not always thoroughly investigate context, she endeavoured to write heteroglossically and to invent a theory that accounted for the music of these songs.